PERTUMBUHAN DAN LAJU EKSPLOITASI IKAN SELAR KUNING (Selaroides leptolepis) DI PERAIRAN SELAT MALAKA KECAMATAN TANJUNG BERINGIN KABUPATEN SERDANG BEDAGAI PROVINSI SUMATERA UTARA - Firza Annisa Nasution; Pindi Patana; Ani Suryanti (AQUACOASTMARINE, 2015)
Highly market demand of Yellowstripe Scad (Selaroides leptolepis) effect overfishing without controling by fishermen. This study has objectives on accesing growth and exploitation rates of Yellowstripe Scad in Malacca Strait Tanjung Beringin Serdang Bedagai. This study was held in three months, from March to May 2015. Data analysis used the ELEFAN I method (Electronic Lenght Frequencys Assesment Tool) by using FiSAT II (FAO-ICLARM Fish Stock Assesment Tool) software. The samples of yellowstripe scad are 572 which consist of 206 female and 366 male. The growth pattern of Yellowstripe Scad is positive allometric. The range of condition factor are 0,7114 - 1,5510. The range of length frequency distribution are 100 – 167 mm, the size group is dominated by 128 – 131 mm for female Yellowstripe Scad and 112 -115 mm for male Yellowstripe Scad. The estimation of Von Bertalanffy growth parameter are (Length Infinity) L∞ of female Yellowstripe Scad is smaller than Length Infinity (L∞) of male Yellowstripe Scad, growth coefficient (K) and teorichical age (t0) of female Yellowstripe Scad is bigger than growth coefficient (K) and teorichical age (t0) of male Yellowstripe Scad. Total mortality (Z) of female Yellowstripe Scad is 5,4 per year and male Yellowstripe Scad is 14,1 per year. The estimation natural mortality (M) of female Yellowstripe Scad is 0,8 per year and male Yellowstripe Scad is 0,5 per year. It shows the estimation of exploitation rates are 0,85 per year for female Yellowstripe Scad and 0,96 per year for male Yellowstripe Scad.Keywords: Growth, Exploitation Rates, Selaroides leptolepis, Malacca Strait.